COECKELBERGH, M. (2021). Ética de la inteligencia artificial. Madrid: Cátedra - Couceiro Monteagudo, Jorge (Daimon Revista Internacional de Filosofia, 2023)
Reseña de: COECKELBERGH, M. (2021). Ética de la inteligencia artificial. Madrid: Cátedra.